Gambaran Gejala Computer Vision Syndrome Pada Mahasiswa S1 Keperawatan Di Masa Pandemi COVID-19 - Febbie Chandra Syahrani; Nursiswati Nursiswati; Hasniatisari Harun (Universitas Malahayati Lampung, 2022)
ABSTRACT The use of digital screens during the Covid-19 pandemic is increasing. If it cannot be controlled, computer vision syndrome can occur, which is a collection of symptoms related to eye problems and other functional disorders. These symptoms are caused by the eye's continuous effort to refocus and have impact on decreasing student learning productivity. The purpose of this study was to describe the synptoms of computer vision syndrome in undergraduate nursing students during the Covid-19 pandemic. The purpose of this study was to describe the synptoms of computer vision syndrome in undergraduate nursing students during the Covid-19 pandemic. The research method used quantitative descriptive on undergraduate students of the Faculty of Nursing, Padjadjaran University (N=604). Consisting of batches 2018, 2019, and 2020. The sampling technique used is total sampling with a response rate of 53.6% (n=324). The instrument used consisted 18 symptoms taken from the concept of computer vision syndrome developed by Suci Febrianti and Teuku Samsul Bahri which were valid and reliable symptoms and shared online. All data are presented by univariate analysis and frequency distribution. The results showed that the most common symptoms occurred in the students of the Faculty of Nursing, Padjadjaran University, namely tired eyes 299 students (90.4%), back pain 244 students (75.3%), and heavy eyes 236 students (72.8%). The conclusion in this study is that students of the Faculty of Nursing, Universitas Padjadjaran have symptoms related to the eye or symptoms other than the eye because the duration of the use of digital screens is quite high. So it is hoped that there will be health education related to prevention of symptoms of computer vision syndrome. Keywords: Computer Vision Syndrome, Nursing, Student ABSTRAK Penggunaan digital screen pada masa pandemi Covid-19 semakin meningkat. Jika tidak dapat dikontrol dapat terjadi computer vision syndrome yaitu kumpulan gejala yang berkaitan dengan permasalahan mata dan gangguan fungsional lainnya. Gejala tersebut disebabkan oleh upaya mata yang terus menerus melakukan refocus dan berdampak terhadap penurunan produktifitas belajar mahasiswa. Tujuan penelitian ini untuk mengetahui gambaran gejala computer vision syndrome pada mahasiswa Keperawatan S1 di masa pandemi Covid-19. Metode penelitian menggunakan deskriptif kuantitatif terhadap Mahasiswa S1 Fakultas Keperawatan Universitas Padjadjaran (N=604). Terdiri dari angkatan 2018, 2019, dan 2020. Teknik sampling yang digunakan yaitu total sampling dengan response rate 53,6% (n=324). ). Instrumen yang digunakan yaitu terdiri dari 18 gejala yang diambil dari konsep computer vision syndrome yang dikembangkan oleh Suci Febrianti dan Teuku Samsul Bahri yang sudah valid dan reliabel serta dibagikan secara online. Seluruh data disajikan dengan analisis univariat dan distribusi frekuensi. Hasil penelitian menunjukan gejala yang paling banyak terjadi pada mahasiswa Fakultas Keperawatan Universitas Padjadjaran yaitu mata lelah 299 Mahasiswa (90,4%), nyeri punggung 244 Mahasiswa (75,3%) serta mata terasa berat 236 Mahasiswa (72,8%). Kesimpulan dalam dalam penelitian ini yaitu Mahasiswa Fakultas Keperawatan Universitas Padjadjaran memiliki gejala terkait pada mata ataupun gejala selain mata karena penggunaaan durasi digital screen cukup tinggi. Sehingga diharapkan adanya pendidikan kesehatan terkait pencegahan gejala computer vision syndrome. Kata Kunci : Computer Vision Syndrome, Keperawatan, Mahasiswa